Synthesis of Boronocysteine - Gibson, Samantha M.; Macmillan, Derek; Sheppard, Tom D. (Synlett, 2018)
Herein we report the first synthesis of protected boronocysteine. The target compound was prepared via copper-catalysed diastereoselective nucleophilic borylation of a sulfinimine. After deprotection to give the amine as the hydrochloride salt, four boronocysteine amide derivatives were prepared through reaction with a variety of different active acylating agents.
Keywords: amino acids; boron; copper; imines; peptides